Rising to the challenge: The critical role of social workers in the face of the HIV/AIDS pandemic - Saloner, KL (Social Work/Maatskaplike Werk, 2002)
This paper discusses the critical role that the social worker has to play in the current HIV/ AIDS context. The writer will specifically examine the social worker’s role in sharing her skills,knowledge and attitudes (hereon SKAs) with different professional bodies. In examining this role, it becomes apparent that the professional SKAs of social workers are insufficient to "go around" and reach all who are in need. His/her role cannot, therefore, purely be one of "treatment provider" or problem-oriented interventionist. In order to effectively redistribute some of the relevant SKAs of the profession, more time and energy need to be channelled into his/her role as educator and skills disseminator. The dissemination of such SKAs may better equip lay and professional people to meet the critical needs of many isolated and alienated South Africans.